The conversational implicatures: A case study of the violations of cooperative principles in a novel “Negeri 5 Menara” by Ahmad Fuadi - Bela Fransiska; Farida Ariyani; Ali Mustofa; Eka Sofia Agustina (Universitas Lampung, 2023)
According to a variety of academic works, implicature is a tool used by pragmatics to address the issue of linguistic meaning. Grice 1975 holds the following opinion. There have been numerous studies on implicature, primarily looking at conventional and conversational implicatures. However, the results of the conversational implicature research in novels, which is characterized by a breach of the cooperative principle, are still ambiguous. As a result, this study aimed to describe the conversational implicatures in Ahmad Fuadi's novel “Negeri 5 Menara” that are marked by violations of the cooperative principles. A qualitative methodology was used to carry out this study. The novel